Klasyczno-nieklasyczny dramat Kaspra Brüloviusa o Juliuszu Cezarze - Bogumił, Izabela (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The article deals with the structure of the Latin tragedy Julius Caesar by Caspar Brülovius, a Pomeranian playwright associated with the Academy in Strasbourg. The text was published in 1616, has as many as 2580 verses and shows historical events that took place over the years: from 46 B.C., when Caesar triumphed, to 30 B.C., when the naval battle of Actium ended. One can get the impression that Brülovius carefully planned the original construction of his work: Acts II and III constitute the actual tragedy about Caesar, probably the closest to ancient plays, with a homogeneous, compact action and one main character. This part of the drama could exist on its own (without the other acts). Act I presents Caesar’s achievements (the conquest of Gaul) and is primarily aimed at educating Strasbourg students. The remaining acts (IV, V) not only pursue didactic goals, but also satisfy the tastes of the audience of the time, who probably liked the strings of death and horrors shown directly on the stage and the interweaving of comic elements with real tragedy. As a whole, Brülovius’ work is a non-classical drama, but Acts II and III, considered as a separate whole, constitute a classical drama.